Effect of lasalocid in rations for growing heifers - D.E. Isbell; J.L. Morrill (Kansas Agricultural Experiment Station Research Reports, 1989)
Sixty-four Holstein heifer calves were used from 10 to 26 wk of age to study the effects of lasalocid on growth and feed consumption. Calves were evaluated weekly for weight gain and feed consumption. Lasalocid-fed heifers gained slightly, but not significantly, more than those that did not receive lasalocid. Their hay consumption was not significantly different than that of the control heifers.; Dairy Day, 1989, Kansas State University, Manhattan, KS, 1989; The 1989 Annual KSU Dairy Day is known as Dairy Day, 1989
Keywords: Dairy Day; 1989; Kansas Agricultural Experiment Station contribution; no. 90-140-S; Report of progress (Kansas Agricultural Experiment Station); 580; Dairy; Lasalocid; Heifers; Growth; Gain